Sodium and Potassium Intake from Food Diaries and 24-h Urine Collections from 7 Days in a Sample of Healthy Greek Adults - Athanasatou, Adelais; Kandyliari, Aikaterini; Malisova, Olga; Pepa, Alex; Kapsokefalou, Maria (Frontiers in Nutrition, 2018)
Objective: The main objective of the present study was to measure sodium and potassium intake, employing 24h and spot urine samples and diary records for seven consecutive days. Methods: For seven consecutive days subjects recorded their food and drink intakes, and recorded and collected all urinations. Food sodium and potassium intake were analyzed in 24h and 6h intervals from wake-up time. Urine indices were analyzed in first morning, 24h and 6h intervals samples over the day from wake-up time. The study took place in Agricultural University of Athens, Greece.163 healthy subjects (age 39 ± 12 years; 74 females) were enrolled in the study. Results: Mean urine sodium excretion was 2803.3±1249.0 mg/day (121.9 ± 54.3 mmol/day) and mean urine potassium excretion was 2152.2 ± 913.3 mg/day (55.2 ± 23.4 mmol/day). The highest potassium concentration was measured in the afternoon, while the lowest sodium concentration was measured in the overnight short time interval. Food sodium intake was 1983.2 ± 814.1 mg/day and food potassium was 2264.5 ± 653.3 mg/day. The sources that contribute most in food sodium intake are dairy products 24%, breads 22% and savory snacks 17%. Conclusions: Strategies should encourage the Greek population to moderate sodium intake and promote potassium intake thus adopting a healthier dietary and lifestyle pattern.